Impacts of Aerosol and Environmental Conditions on Maritime and Continental Deep Convective Systems Using a Bin Microphysical Model. Issue 12 (16th June 2020) - Iguchi, Takamichi; Rutledge, Steven A.; Tao, Wei‐Kuo; Matsui, Toshi; Dolan, Brenda; Lang, Stephen E.; Barnum, Julie
Abstract: A series of model simulations were conducted to investigate the effects of cloud condensation nuclei (CCN) loading and convective available potential energy (CAPE) on tropical maritime and midlatitude continental deep convection. Dynamical downscaling from global aerosol reanalysis was used to represent aerosol fields for the two convective regimes. We describe a control run and multiple sensitivity experiments using a limited‐area model, employing spectral‐bin cloud microphysics. The CCN loading is perturbed between the target maritime and continental conditions, roughly 40–2, 000 cm −3 at 850 hPa and 1% supersaturation. Surface precipitation rates monotonically increase with increasing CCN loading for both the maritime and continental situations, while these monotonic increases are disrupted in the simulations with reduced CAPE. The increase in precipitation is in the form of convective precipitation, at the expense of stratiform precipitation. CCN increases promote increases in supercooled cloud water, in agreement with previous modeling studies. However, in the simulations investigated herein, the changes in supercooled water have different impacts on the cloud microphysics in the maritime and continental simulations. Increased supercooled water contents lead to more hail and less graupel in the continental simulation. For the maritime simulation, enhanced supercooled cloud water contents promote an increase in graupel since little or no hail is produced. This distinction is due to the difference in relative magnitudes and peak altitudes of supercooled water and snow amounts, which is further attributable to moisture and dynamical differences in the two cases. Key Points: Impacts of aerosol and thermodynamics conditions on deep convective systems are investigated using a bin microphysical model Increasing aerosol concentrations promote stronger convective precipitation in both the maritime and continental case Increasing aerosol concentrations increases graupel (hail) in maritime (continental) case owing to height of snow‐dominant layer